Pengaruh Luka Iris Pada Tikus Dengan Paparan Hidrogen Peroxida 3% terhadap Epitelisasi dan Pembentukan Eksudat pada Permukaan Epitel Kulit - HARMAN AGUSAPUTRA; MARIA SUGENG; AYLI SOEKAMTO; ATIK WULANDARI (HANG TUAH MEDICAL JOURNAL, 2020)
Abstract Background: Hydrogen peroxide (H2O2) as antiseptic has been used frequently to clean woundsin in hospitals and clinics. Hydrogen peroxide has the effectof strong oxidative that can kill pathogens. It can clean up debris and necrotic tissuesin wounds. Hydrogen peroxidealso has hemostatic effect that can help to stop bleeding. Besides antiseptic effects, hydrogen peroxide i s suspected of having negative effect in wound healing. Hydrogen peroxide presumably could cause delayed wound healing by exudate formation and delayed epithelial growth. Method: This study was conducted in the laboratory using 48 white mice that were divided into 2 groups. All the mice were purposely wounded. Afterwards in one group the wounds were clean up using hydrogen peroxide, while in the other group without hydrogen peroxide as control. The wounds of both groups were observed on day 1, day 3 and day 7. On day 1 and day 3, both groups did not show significant difference. Result : on day 7 showed that the wound healing in hydrogen peroxide group were delayed. Fifty percent of them had the formation of exudate and 62.5% of them showed delayed epithelial growth. Conclusion : This study could show hydrogen peroxide as wound antiseptic has delayed wound healing effect.